The Effect of Giving “Semundu” Juice with a Combination of Probiotics on Blood Pressure in Pre-Hypertension Patients - Septia, Reka; Maigoda, Tonny C; Krisnasary, Arie; Hariadi, Hari (Applied Research in Science and Technology, 2024)
Hypertension is a medical condition characterized by elevated blood pressure beyond normal limits. Management strategies for hypertension can be pharmacological or non-pharmacological. This study aims to evaluate the effect of administering "semundu" juice combined with yogurt on reducing blood pressure in individuals with hypertension in the Jembatan Kecil Health Center area, Bengkulu City, in 2024. A total of 28 participants with high blood pressure were randomly assigned to one of four groups: P0 (control group receiving educational leaflets), P1 (200g watermelon juice, 100g cucumber, and 20ml honey), P2 (100g Ambon banana, yogurt), and P3 (200g watermelon juice, 100g cucumber, 20ml honey, and yogurt). The Kruskal-Wallis test results indicated that the administration of "semundu" juice combined with probiotics significantly affected both systolic and diastolic blood pressure, as evidenced by a p-value of less than 0.05. All treatment groups demonstrated a reduction in blood pressure, with significant differences observed between the groups: P0 vs. P3 (p-value < 0.02), P1 vs. P3 (p-value < 0.034), and P2 vs. P3 (p-value < 0.01). These findings suggest that "semundu" juice combined with probiotics has a notable impact on lowering blood pressure in individuals with hypertension.